The national income of Sudan 1955/56 - 1959/61: (with preliminary estimates for 1960/61) - H.Q Council of Ministers; Department of Statistics (Khartoun Dept of Statistics, the Republic of the Sudan, 1962)
National income of Sudan (in brief) 1955/56
aia 29/03/2019
Loans
Keywords: Income distribution-- Sudan; Public Finance; National income; Sudan